Analysis of clinical characteristics of 617 patients with benign airway stenosis - Wei, Jinmei; Qin, Shujuan; Li, Wentao; Chen, Yan; Feng, Tingmei; Wei, Yuhui; Tan, Sen; Liu, Guangnan (Frontiers in Medicine, 2023)
Introduction Benign airway stenosis (BAS), namely airway narrowing caused by a variety of benign lesions, can lead to varying degrees of breathing difficulties and even death due to asphyxia. This study aimed to elucidate the clinical characteristics of BAS, including etiology, treatment and pathology, by analyzing the clinical data of BAS patients. Methods A retrospective analysis was conducted using the clinical data of 617 BAS cases from January 2017 to December 2022. The pathological characteristics of the tissues were assessed by hematoxylin–eosin (H&E) and Masson’s staining. Besides, protein expression levels were determined by immunohistochemistry (IHC). Results A total of 617 patients were included (333 females [53.97%] and 284 males [46.03%]), with an average age of 48.93 ± 18.30 (range 14–87). Tuberculosis (n = 306, 49.59%) and trauma (n = 179, 29.02%) were the two leading etiologies of BAS, followed by airway foreign bodies (FB, n = 74, 11.99%), external compression (n = 25, 4.05%) and other etiologies (n = 33, 5.35%). Among 306 tuberculous tracheobronchial stenosis (TBTS) cases, most were females (n = 215, 70.26%), and TBTS mainly occurred in the left main bronchus (n = 97, 31.70%), followed by the right middle bronchus (n = 70 cases, 22.88%). The majority of TBTS patients (n = 259, 84.64%) were treated by interventional therapy. The condition of 179 BAS patients was ascribed to trauma, such as tracheal intubation (n = 92, 51.40%), tracheotomy (n = 69, 38.56%), injury (n = 15, 8.38%) and surgery (n = 3, 1.68%), which mostly took place in the trachea (n = 173, 96.65%). TAS patients mainly received interventional therapy (n = 168, 93.85%) and stent implantation (n = 47, 26.26%). The granulation tissues of BAS primarily featured inflammation, proliferation and fibrosis. IHC indicated the up-regulated expressions of transforming growth factor-β1 (TGF-β1), α-smooth muscle actin (α-SMA), collagen type I protein (COL-I) and vimentin, and the down-regulated expression of E-cadherin, which indicated fibrosis and epithelial-mesenchymal transition (EMT). Conclusion Tuberculosis was the main etiology, and trauma was the secondary etiology. The granulation tissues of BAS were characterized by inflammation, fibrosis and probably EMT. Comprehensive interventional therapy is an effective method of treating BAS.